Child and family factors that predict participation attendance in daily activities of toddlers with global developmental delay. Issue 13 (19th June 2021) - Wang, Pei-Jung; Liao, Hua-Fang; Kang, Ling-Ju; Chen, Li-Chiou; Hwang, Ai-Wen; Lu, Lu; Tu, Yu-Kang; Morgan, George A.
Abstract: Purposes: Enhancing children's daily participation is the optimal goal of early childhood intervention. This study aimed to identify child and family predictors of participation for toddlers with global developmental delay. Methods: Fifty-nine toddlers with global developmental delay (aged 24–43 months) and their mothers participated in a 6-month longitudinal study. Predictors for participation were child factors [age, gender, delay severity, mastery motivation (perceived persistence and task persistence), and withdrawal behavior], and family factors (socioeconomic status, family income, maternal education, stress, and maternal teaching behavior). Dependent variables were participation diversity and intensity of four activity types measured 6-month later using the Assessment of Preschool Children's Participation (Chinese version). Correlation and hierarchical regression statistical methods were used. Results: Older children with higher persistence had higher overall participation. Different factors predicted different participation dimensions and different activity types. Older age, higher perceived persistence, and being less withdrawn predicted higher diversity and intensity for play participation. For skill development participation, older age, less severity, higher mastery motivation, and better maternal teaching behaviors predicted higher diversity; and age, mastery motivation and maternal teaching predicted intensity. Conclusions: Different factors predict participation attendance differently. Supporting parents to enhance toddlers' mastery motivation may optimize children's participation in daily activities. Implications for rehabilitation: Based on the child and their caregiver preferences, applicability and/or engagement for different activity types, interventionists could collaborate further with caregivers to find strategies to increase children's participation attendance in daily life. Interventionists could consult with caregivers: (a) to observe the persistence and positive affect (mastery motivation) of children during different activities, (b) to figure out the possible barriers to participation in those activities, and (c) to demonstrate appropriate caregiver-child interactions. Interventionists are encouraged to support children's mastery motivation and quality of maternal teaching behaviors to enhance participation in daily activities.